Antimicrobial efficacy of synthetic and natural-derived novel endodontic irrigating solution - An In vitro study - Thangi Sowjanya; Sudhakar Naidu; Mahendra Varma Nadimpalli; Gowtam Dev Dondapati; T B V G Raju; Parvathaneni Krishna Prasad (Wolters Kluwer Medknow Publications, 2020)
Aim and Objective: This in vitro study was designed to comparatively evaluate the antimicrobial efficacy of peracetic acid (PAA - 0.5% and 1%), phytic acid (IP6 - 0.5% and 1%), and sodium hypochlorite (NaOCl - 3% and 5.25%) as irrigating agents against Enterococcus faecalis. Materials and Methods: Agar plates were prepared using Mueller-Hinton (MH) agar. E. faecalis injected in nutrient broth at 37°C. Well diffusion methods were used to derive results. Plates were inoculated for 36 h at 37°C, and microbial zones of inhibition were recorded. Statistical analysis was performed with repeated measures of analysis of variance. Results: PAA (1%) and IP6 (1%) showed larger zones of microbial inhibition. PAA (0.5%) was statistically significant (P < 0.05) when compared to NaOCl (3% and 5.25%). Conclusion: PAA (1%) was used as an irrigating agent in endodontic failure cases.